Risk and Income Analysis of Vaname Shrimp Cultivation Business (Litopenaeus vannamei) in Bantan District, Bengkalis Regency - Sarah, Maya; Arief, Hazmi; Yanti, Chicka Willy (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
This research was conducted in April 2025 in Bantan District, Bengkalis Regency. This study aimed to calculate the income of vaname shrimp farming and analyze the production and income risk of vaname shrimp farming. The survey method was used in this study. The risk measures used include variance, standard deviation, coefficient of variation, and lower limit, while business income is analyzed using income analysis. The number of samples was 26 respondents, with the selection of census technique samples. The results showed that the respondents' average production of vaname shrimp was 660,558.85 kg/Ha, and the average income was IDR614,516,253 / ha. The coefficient of variation of the results of production risk analysis is 0.0887, with a lower limit of 20,896 kg/Ha. The coefficient of variation from the results of the income risk analysis is 0.1139 with a lower limit of IDR474,445,189/Ha. From the study results, the risk to the production and income of Vaname shrimp farming is relatively low